Pemanfaatan Digital Parenting Internet Yang Sehat Bagi Anak-Anak Sekitar Kelurahan Sukasari - Tri Santoso; Sulistianto SW; Andi Sanjaya (CV. Multi Kreasi Media, 2025)
In today's increasingly advanced digital era, the use of the internet has become a very important part. Human life cannot be separated from the internet network. Because, the internet is a network system that can connect one device to another. In addition to computers, the internet can now also connect various gadgets and serve billions of users worldwide. The existence of the internet allows someone to search for the information they want. For example, looking for the latest news or accessing streaming services to watch their favorite drama series. However, the internet can have positive or negative impacts depending on the user. The internet has become a major component that supports the activities of modern society today. There are many impacts caused by children often accessing the internet, especially social media. This not only has positive but also negative impacts. For children who are able and understand the internet, they are more likely to use the internet positively, such as searching for information related to useful things such as the lessons they are studying. Meanwhile, one of the negative impacts is that children become addicted and spend a long time in cyberspace, looking for new things that are not appropriate for their age, even children access pornographic sites, cyberbullying and other negative impacts.